Drying of sisal fibers in fixed bed: a predictive analysis using lumped models (Research, Society and Development, 2020)
Sisal fibers have inspired the interest of academia and industry, due to their excellent characteristics for use in various applications. These fibers, when extracted from the plant, are moist and are subjected to drying to reduce the moisture content. The control of the drying process is of great importance to guarantee the quality of the fibers in terms of mechanical strength and color. In this sense, this work aims to theoretically study the drying of sisal fibers in an oven with forced air circulation. Mathematical models have been proposed to predict the transient behavior of the average moisture content and surface temperature, and the equilibrium moisture content of the fibers, as a function of the drying air temperature and water vapor concentration in the fiber bed. Predicted results of drying and heating kinetics, and the hygroscopic equilibrium moisture content of the fibers are presented and compared with the experimental data, under different operational conditions. It was found that a good fit was obtained, with a correlation coefficient greater than 0.99, for all models analyzed.